Preparedness action of small and medium enterprises (smes) in the food industry to confront the covid-19 pandemic - Harun, Nur Hafizah; Sahari, Noorul Huda; Mamat, Norazlina; Mohd. Aris, Suliah; Mazlan, Farhaneen Afzal (Penerbit UiTM, 2022)
The COVID-19 pandemic is the greatest threat to global health. It has a farreaching socio-economic impact on nearly all countries globally. The first case was reported in Malaysia on 25 January 2020. The number of issues kept increasing until the government announced the Movement Control Order (MCO) on 18 March 2020. As a result, the closures have had a major impact on businesses, especially small and medium enterprises (SMEs). This COVID19 pandemic greatly impacted worldwide compared to the H1N1 pandemic outbreak in 2009. This study aimed to examine the concept of preparedness actions of SMEs in the food industry to confront the COVID-19 pandemic. The study adopts a qualitative method of collecting data through documentation and library research to achieve this objective. The data consists of primary and secondary data gathered from books, articles, journals, reports, newspapers, and online databases. The findings of this study indicated that preparedness actions could be divided into survival and mitigation actions. Survival actions cover financial planning, business operations, and crisis preparation actions. Meanwhile, to mitigate the impact of COVID-19 on business, the preparedness actions needed are assessing the impact of the pandemic on the organizations from operational and financial perspectives, evaluating the supply chain, and identifying potential points of failure. The outcome of this study is significant in terms of enhancing the knowledge of preparedness of SMEs in confronting the COVID-19 pandemic outbreak.